Developing Entrepreneurial Intelligence Among Retirees of the Bukittinggi City Government - Stevani Stevani; Vivina Eprillison; Dina Amaluis; Jimi Ronald; Mona Amelia (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2024)
While "retirement" is an Indonesian term for someone who has retired—that is, someone who abandoned their job after reaching a particular age or for health or other reasons—entrepreneurship is an activity that tries to promote the welfare of society in the sense of a better quality of living. In recognition of their years of service, they typically get a pension or allowance from the government or the business where they once worked. The purpose of this exercise is to enable the women and gentlemen of the Bukittinggi city administration to continue being innovative and involved in business once they retire.